A Family of Dinuclear Iron(II) SCO Compounds Based on a 1, 3, 4‐Thiadiazole Bridging Ligand (Eur. J. Inorg. Chem. 22/2015). Issue 22 (5th August 2015) - Herold, Christian F.; Carrella, Luca M.; Rentschler, Eva
Abstract : The cover picture shows a new dinuclear iron(II) SCO compound as a molecular switch. The 1, 3, 4‐thiadiazole backbone of the bridging ligand was necessary to achieve the diamagnetic [LS–LS] ground state, so far not observed in related systems. The two complexes illustrate temperature‐dependent spin state switching upon cooling with ice or heating with fire. We highly acknowledge Dipl.‐Chem. Denis Bittner for the graphic realization of the cover picture. Details are discussed in the Short Communication by E. Rentschler et al. onp. 3632 ff . For more on the story behind the cover research, see theCover Profile .